(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
This study investigates the fabrication of chitosan (CS)/polyvinyl alcohol (PVA) blend nanofibers via electrospinning, aiming to create nanofibers with enhanced properties for broad applications. The research focuses on optimizing electrospinning parameters to reduce bead formation and achieve uniform nanofiber morphology. A detailed experimental design, employing a nineteen-point plan developed with Design-Expert software, examined variables such as polymer concentration, distance from the needle to the collector, the required voltage, and the rate at which solution was ejected from the needle. Morphological characteristics of the nanofibers were analyzed using advanced microscopy, complemented by drug release and wound healing assessments. The optimal electrospinning conditions were determined to be a 1:3 CS/PVA solution concentration ratio, an 8 cm needle-to-collector distance, a 20 kV applied voltage, and a 1 mL/hour flow rate. Scanning electron microscopy revealed uniform nanofibers with diameters between 100 to 250 nm, devoid of bead defects. In-vitro analysis demonstrated a sustained release profile of azilsartan (AZL), while in-vivo studies on rats indicated enhanced wound healing, corroborated by histological examination. The findings suggest that CS/PVA nanofibers, fabricated under these conditions, possess promising characteristics for use as a drug-delivery scaffold in wound treatment applications.